2012
DOI: 10.1016/j.neuroscience.2012.09.049
|View full text |Cite
|
Sign up to set email alerts
|

C1 catecholamine neurons form local circuit synaptic connections within the rostroventrolateral medulla of rat

Abstract: C1 catecholamine neurons reside within the rostroventrolateral medulla (RVLM), an area that plays an integral role in blood pressure regulation through reticulospinal projections to sympathetic preganglionic neurons in thoracic spinal cord. In a previous investigation we mapped the efferent projections of C1 neurons, documenting supraspinal projections to cell groups in the preautonomic network that contribute to the control of cardiovascular function. That light microscopic study also revealed putative local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 71 publications
0
10
0
4
Order By: Relevance
“…Some C1 neurons are interconnected by recurrent collaterals (123). The presence of PNMT-ir synapses within the RVLM/ IVLM was first described by Milner et al (123) and has been recently confirmed (5). These connections may contribute to the tendency of sympathetic vasomotor efferents to discharge synchronously in vivo, even in the absence of baroreceptor input and respiratory network activity (19).…”
Section: Projections Of the C1 Neuronsmentioning
confidence: 86%
See 2 more Smart Citations
“…Some C1 neurons are interconnected by recurrent collaterals (123). The presence of PNMT-ir synapses within the RVLM/ IVLM was first described by Milner et al (123) and has been recently confirmed (5). These connections may contribute to the tendency of sympathetic vasomotor efferents to discharge synchronously in vivo, even in the absence of baroreceptor input and respiratory network activity (19).…”
Section: Projections Of the C1 Neuronsmentioning
confidence: 86%
“…At present, the best documented aspect of C1 cell communication is their "wiring transmission" (201), which operates via conventional ionotropic glutamatergic synapses and likely accounts for the short-term effects that have been attributed to C1 cell activation in vivo; i.e., short time-scale sympathetic reflexes and acute AP stabilization (66,128). The axonal varicosities of the C1 cells typically form conventional synapses; e.g., in the IML, locus coeruleus, rostral ventrolateral medulla (RVLM), and DMV (5,52,(121)(122)(123). These synapses are usually (75%) asymmetric and the C1 neurons express vesicular glutamate transporter-2 (VGLUT2) mRNA and lack markers of inhibitory neurons such as glutamic acid decarboxylase (GAD), and glycine transporter 2 (GlyT2) (39,160,176,178).…”
Section: Signaling By the C1 Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results agree with these reports and other reports detailing subsets of C1 projections in rats including e.g. to the dorsal motor nucleus of the vagus (Pickel et al 1986) (note Ruggiero found C1 with collaterals to spinal cord project to DMV/NTS (Mtui et al 1995)), the NTS (Rukhadze and Kubin 2007), raphe pallidus (Luppi et al 1989), the PAG (Clement et al 1998; Herbert and Saper 1992), locus coeruleus (Milner et al 1989; Holloway et al 2013), A1 (Holloway et al 2013), and local connections within the C1 area (Agassandian et al 2012). We also noted that both subsets of C1 neurons targeted all the other catecholaminergic cell groups in medulla/pons (A1, A2, C1, C2, C3, A5, A6).…”
Section: Discussionmentioning
confidence: 98%
“…No entanto, embora os neurônios C1 expressem o fenótipo catecolaminérgico, evidências funcionais e anatômicas indicam que estes neurônios utilizam o glutamato como principal neurotransmissor Guyenet et al, 2013;Holloway et al, 2013;Abbott et al, 2014;Holloway et al, 2015). Os terminais que expressam PNMT, os quais também expressam glutamato, formam contato sináptico assimétrico, consistente com a ultraestrutura de sinapses excitatórias glutamatérgicas clássicas, reforçando a hipótese de que os neurônios C1 atuam por meio de sinapses glutamatérgicas (Milner et al, 1987;Milner et al, 1988;Agassandian et al, 2012;Depuy et al, 2012;Abbot et al, 2014). Além disso, tem sido consistentemente demonstrado que as respostas promovidas pela ativação seletiva dos neurônios catecolaminérgicos do grupamento C1 são desencadeadas por sinalização glutamatérgica Guyenet et al, 2013;Holloway et al, 2013;Abbott et al, 2014;Holloway et al, 2015).…”
Section: Ilustração 1 -Grupamento Adrenérgico C1: Definição E Localizunclassified